THE ROLE OF BUSINESS STRATEGY MEDIATES INDUSTRY COMPETITIVE INTENSITY AND RESOURCE AVAILABILITY ON BUSINESS PERFORMANCE - Yasa N.N.K.; Sukaatmadja I P.G.; Subawa I K.; Febrianti A.T.; Rahmayanti P.L.D. (Eurasia: Economics & Business, 2023)
The objective of this study was to investigate how business strategy mediates the influence of industry competitive intensity and resource availability on the performance of small and medium enterprises (SMEs), particularly endek handicrafts in Bali. The target population for this study consists of endek handicrafts SMEs in Bali that have implemented a comprehensive business strategy. Purposive sampling was utilized in selecting a sample of 170 SME managers of endek handicrafts. Path Analysis using SEM-PLS is the analysis method used. The findings indicated that business performance was negatively and significantly impacted by the industry's competitive intensity. The performance of a business is positively and significantly impacted by resource availability. Business strategy also affects the effectiveness of a business's performance. The impact of the industry's competitive intensity and resource availability on business performance may also be mediated by business strategy. In order to significantly improve their business performance, endek handicraft SMEs in Bali need to establish a thorough business strategy.